(untitled) (Research, Society and Development, 2022)
It can be observed that many difficulties are encountered by high school students, by the teacher, by other school professionals and by the community during the supervised curricular internships, in the Licentiate courses. There are problems that can involve both didactic in teaching, as well as structural aspects of the schools. These issues can directly interfere in the quality of education. In this work, a qualitative research was carried out, and it was analyzed the final reports of the Supervised Curricular Internship of the students of a degree in chemistry, to observe the main difficulties in the teaching experience, which could interfere in the quality of teaching. With regard to the teaching of Chemistry, it was observed, among other factors, the use of exclusively expository and traditional classes. The study of teaching quality indicators can broaden the view on some important factors that directly affect the improvement of teaching, whether in the discipline of Chemistry or in other areas.